2014
DOI: 10.1155/2014/420149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clinical Periodontitis and Putative Periodontal Pathogens among South Indian Pregnant Women

Abstract: In view of recent understanding of the association of periodontal infections and adverse pregnancy outcomes, the present investigation was undertaken to study the periodontal infections among 390 asymptomatic pregnant women and to find an association of bacterial etiologies with the disease. Prevalence of gingivitis was 38% and clinical periodontitis was 10% among the study population. Subgingival plaque specimens were subjected to multiplex PCR targeting ten putative periodontopathogenic bacteria. Among the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
0
18
1
3
Order By: Relevance
“…These detection rates were higher than Tellapragada et al ’s study16 which also investigated prevalence of putative periodontopathic bacteria among pregnant women with periodontitis in India. Since the mean age and gestational age between the present study and study conducted in India were similar (age: 26.9 ± 3.6  vs. 26 ± 3.4 years; Gestational age: 18.3 ± 7.5  vs. 18 ± 3.5 weeks), the possible explanations for the different detection rates were due to different ethnic group and diagnostic criteria for chronic periodontitis.…”
Section: Discussioncontrasting
confidence: 55%
“…These detection rates were higher than Tellapragada et al ’s study16 which also investigated prevalence of putative periodontopathic bacteria among pregnant women with periodontitis in India. Since the mean age and gestational age between the present study and study conducted in India were similar (age: 26.9 ± 3.6  vs. 26 ± 3.4 years; Gestational age: 18.3 ± 7.5  vs. 18 ± 3.5 weeks), the possible explanations for the different detection rates were due to different ethnic group and diagnostic criteria for chronic periodontitis.…”
Section: Discussioncontrasting
confidence: 55%
“…P. gingivalis and T. denticola were found at a significantly higher level among the pregnant women with periodontitis [221]. Recent metagenomic analysis studies revealed that placental microbiome profiles were similar to the oral microbiome [242].…”
Section: Periodontal Diseases and Gdmmentioning
confidence: 96%
“…The prevalence of gingivitis in pregnant women has reportedly ranged from 30% to 100% [220]. Globally, 40% to 60% of females experience gingivitis during their pregnancy [221]. The severity of pregnancy-related gingivitis usually increases in the second trimester.…”
Section: Periodontal Diseases and Gdmmentioning
confidence: 99%
See 2 more Smart Citations